Couva river diversion : a problem in environmental planning - McShine-Mutunhu, Hazel (Institute of Marine Affairs ChaguaramasTT, 1985)
Determines and assesses the ecological, sociological, & environmental impacts that result from the damming and diversion of the Couva river in central Trinidad. Alteration of the natural drainage system; loss of wetlands and feeding grounds for fish are cited as some of the ecological impacts. The destruction of mangroves and loss of shellfich trade; the accumulation of untreated wastes in the lake and the blocking of the Carli bay access road create sociological impacts. Makes recommendations for the environmental management of Carli bay.